Digital inequality and neighborhood divides in online social networks in Chicago - Karl Vachuska (Scientific Reports)
Abstract The use of social media has increasingly become a central part of how individuals access and disseminate information. Because the United States is heavily stratified by place, which social media can transcend, some have suggested that social media may alleviate spatial inequalities. The present study builds on this notion by exploring the relationship between Twitter networks and neighborhood and racial inequality in access to information in the city of Chicago. Combining public records with Twitter data, I constructed a geocoded network of 86,336 Chicago Twitter users. My findings indicate that users in Black and Hispanic neighborhoods tend to be less connected to the network, both in terms of out-degree and in-degree, suggesting a potential divide in terms of information access and dissemination. I further identify two mechanisms that likely facilitate the segregation of information between different racial groups: racial homophily in Twitter following and racial selection in message transmission. This study highlights the need to further explore the intersections of race, place, and social media in understanding inequalities in the digital age.